Comparison of TP53 mutations screening by functional assay of separated allele in yeast and next-generation sequencing in myelodysplastic syndromes. Issue 11 (November 2015) - Bally, Cécile; Renneville, Aline; Preudhomme, Claude; Legrand, M.; Adès, Lionel; de Thé, Hugues; Fenaux, Pierre; Lehmann-Che, Jacqueline
Highlights: FASAY and NGS detect TP53 mutations not identified by the other method. FASAY can detect ins/del not well detected by NGS. NGS can detect small mutated clones not detected by FASAY. The two methods appear complementary. Abstract: TP53 mutations are major prognostic factors in many hematological malignancies including acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS). Next-generation sequencing (NGS) has improved the detection of such mutations by identifying small mutated clones but functional method like FASAY (functional assay of separated allele in yeast) may prove interesting. We compared the detection of TP53 mutations by FASAY and NGS in 91 patients with AML or MDS. By FASAY, 91% of assays were evaluable and 47 patients (57%) had a functional and 36 (43%) a non-functional p53 protein. FASAY could not conclude in 8 cases (9%), mainly because of poor RNA quality. No TP53 mutation was found using NGS in 50 cases (55%), and at least one mutation was detected in 41 cases (45%). The p53 status was concordant between FASAY and NGS in 95% (79/83) of cases. The four discordances included mutations detected by FASAY only in two cases, and by NGS only in two cases. Mutations not detected by NGS consisted of insertions in intronic regions, which were not analyzed by this assay. Mutations not detected by FASAY were mutations for which the percentage of mutated allele was less than 10%, including one mutation reported as non-deleterious in the IARC database. Overall, our data suggest that FASAY is an effective and reliable method to detect TP53 mutations in AML and MDS, which allows the assessment of the protein functionality, contrary to a sequencing approach.